Overcoming Cost Implications of Mutational Analysis in Patients with Gastrointestinal Stromal Tumors: A Pragmatic Approach - Schöffski, Patrick; Wozniak, Agnieszka; Schöffski, Oliver; van Eycken, Liesbet; Debiec-Rychter, Maria (Oncology research and treatment, 2016)
BACKGROUND: Genetic analysis of tissue derived from patients with advanced gastrointestinal stromal tumors (GISTs) is not uniformly applied on a national and international level, even though mutational data can provide clinically relevant prognostic and predictive information, especially in patients qualifying for treatment with expensive targeted agents. METHODS:The current article describes the rationale for genetic testing of GIST tissue, looks at financial implications associated with such analysis and speculates on potential cost savings introduced by routine mutational testing and tailored use of tyrosine kinase inhibitors based on genotyping. This work is based on a hypothetical analysis of epidemiological data, drug costs, reimbursement criteria and market research figures. RESULTS: The cost burden for routine genotyping of important genes in GISTs, especially in patients at high risk for relapse after primary surgery and in advanced, inoperable metastatic disease, is relatively low. The early identification of GISTs with primary resistance mutations should be the basis for personalized GIST treatment and reimbursement of drugs. As illustrated by Belgian figures, the exclusive use of a drug such as imatinib in patients who are likely to benefit from the agent based on genetic information can lead to significant cost savings, which outweigh the costs for testing. CONCLUSIONS: Mutational analysis of GIST should be considered early in all patients at risk for relapse after curative surgery and in the case of advanced, inoperable, metastatic disease. The costs for the actual genotyping should not be used as an argument against profiling of the tumor. The adjuvant and palliative systemic treatment of GISTs should be personalized based on the genotype and other known prognostic and predictive factors. Reimbursement criteria for essential agents such as imatinib should be adapted accordingl